Geochemistry, zircon U–Pb ages and Sr–Nd–Hf isotopes of an Ordovician appinitic pluton in the East Kunlun orogen: New evidence for Proto-Tethyan subduction. (1st November 2015) - Xiong, Fuhao; Ma, Changqian; Wu, Liang; Jiang, Hong'an; Liu, Bin
Highlights: Appinites in the South Kunlun suture zone were emplaced at 447–450 Ma. Appinites were generated by partial melting of metasomatised mantle wedge. Subduction of the South Kunlun Proto-Tethyan ocean did occur in Late Ordovician. Abstract: Appinite is commonly derived from a mantle source in subduction zones and thus holds a key to constrain the tectonic evolution of ancient orogens. This study presents chronological, mineralogical and geochemical data for one appinitic pluton from the south Tethyan suture zone in the East Kunlun orogen, Northern Tibetan Plateau. The pluton is predominantly composed of hornblende-rich mafic appinites, with minor amounts of granodiorite. Zircon U–Pb age of the granodiorite (466 Ma) is identical to the mafic appinites (447–450 Ma). The mafic appinites are commonly hornblende diorites, which comprise large amounts of magnesio-hornblende [Mg/(Fe + Mg) = 0.61–0.68] and andesine (An43–54 ). The hornblende diorites have low contents of SiO2 (48.62–54.95 wt.%), high contents of total FeO (7.90–12.84 wt.%) and MgO (4.32–11.89 wt.%) and moderate values of Mg # [Mg # = molar 100 ∗ Mg/(Mg + Fe); 49–69]. Their geochemistry displays: slight enrichment of light rare earth elements ((La/Yb)N = 1.89–6.84) and flat heavy rare earth elements ((Ga/Yb)N = 1.49–2.22); enrichment in large ion lithophile elements and depletion in high field strength elements; less-enriched isotopic compositions with initial 87 Sr/ 86 Sr ratios of 0.70536–0.70617, ε Nd ( t ) of 0.79–3.02 and zircon ε Hf ( t ) of 8.73–12.82. The associated granodiorites comprise plagioclase (45–50 vol.%, An = 26–39), quartz (15–20 vol.%), K-feldspar (5–10 vol.%), ferrohornblende [2–5 vol.%, (Mg/(Fe + Mg) = 0.45–0.49] and epidote (1–5 vol.%). The epidotes have pistacite components ranging from 23 to 28. The granodiorites exhibit calc-alkaline character, and have rare earth and trace element patterns similar to the hornblende diorites. The geochemical compositions and simulations suggest that the parental magma of the mafic appinites was generated by partial melting of one depleted mantle source which was metasomatised by subducted sediment-derived felsic melts (ca. 20–25%). Fractional crystallization of clinopyroxene, hornblende, magnetite and titanite has driven the appinitic magma to cogenetic granodiorite. The Late Ordovician mafic appinites indicate that there did exist Proto-Tethyan subduction along the South Kunlun suture zone, and the subduction would add significant volumes of sediment-derived melts into the depleted mantle wedge, resulting into metasomatism and melting with the formation of appinitic magma.